Desenvolvimento de um reator fotoquímico microcontrolado, utilizando diodos emissores de luz (LEDs) como fonte de excitação luminosa - Possatto, João Fernando (Universidade Federal de São Carlos, 2011)
Aiming to contribute to the technological development of our country and meet the domestic demand for photochemical reactors, we have considered the possibility of developing a national product. The development of this project required the acquisition of knowledge to master the technology employed in the construction and application of photochemical reactors. This process was followed by refinement and implementation of the innovations that would make them more competitive and versatile to meet the demands of today s market. In the elaboration of the reactor, appropriate tools and the latest computing resources, comprising all stages of the project, namely structural design, loaded electronic and firmware were employed. Then it was possible to construct a virtual prototype with all the benefits of a real product, which enabled the construction of a physical one. As a result, the user could benefit from the combination of nice design and functional structure together with smart and efficient electronics and simple, intuitive interface. Results have proved not only the equivalence, but also the increase in the luminous efficiency through the substitution of the traditional radiation source of the fluorescent light by the LED light source (Light Emitting Diodes). So, through the implementation of the LED technology to this equipment, important and fundamental innovations were made, as follows. Clean, mercury-free and recyclable technology. Greater efficiency in turning electrical energy into luminous energy, leading to reduced electricity consumption and low heat generation. Greater durability of LED light sources, up to 1000 times higher when compared to fluorescent bulbs. Implementation of microcontroller systems, promoting control of luminous intensity, time-programmed excitation, temperature checking, graphical interface etc. The completion of this project resulted in the construction of a photochemical reactor which will bring a number of technological innovations to our country.
Keywords: Fotoquímica; Reatores químicos; Reatores fotoquímicos a LEDs; CIENCIAS EXATAS E DA TERRA::QUIMICA